Enseigner l’écriture en milieu francophone minoritaire : comment motiver les élèves et surmonter les défis de l’insécurité linguistique ? - Blain, Sylvie; Cavanagh, Martine; Cammarata, Laurent (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
Teaching writing in elementary and secondary schools is a challenge in all sectors of education, among other reasons because the writing activities offered at school are not always motivating according to students. Francophone schools in a minority context face the same problem, but also the difficulty of overcoming linguistic insecurity. In this critical reflection, we will build on theories of instructional motivation, as well as the most recent research results on learning to write in a minority milieu, to offer some potential solutions for elementary and secondary French teachers.